2017
DOI: 10.1021/acs.est.7b04657
|View full text |Cite
|
Sign up to set email alerts
|

External Exposure to Short- and Medium-Chain Chlorinated Paraffins for the General Population in Beijing, China

Abstract: Chlorinated paraffins (CPs) are a class of compounds that are currently produced and used in large amounts in commercial products worldwide. In this study, food, indoor air, indoor dust, and drinking water samples were collected to evaluate the external exposure levels of CPs and possible pathway for the general population in Beijing, China. Short chain CPs (SCCPs) and medium chain CPs (MCCPs) in 199 samples were analyzed using a gas chromatography tandem time-of-flight high-resolution mass spectrometry (GC-TO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
117
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(138 citation statements)
references
References 33 publications
13
117
5
Order By: Relevance
“…Likewise, offices and homes had comparably low ∑SCCP concentrations ranging 5-31 and 11-14 µg/g in a limited number of Taiwanese dust samples (n=4) [16]. On the other hand, reported offices to be the least contaminated indoor environments amongst Chinese indoor microenvironments assessed with respect to both SCCP and MCCP homologues [29]. CP levels measured in a limited number of office samples from outside China have usually exceeded levels seen in homes.…”
Section: Chlorinated Paraffinsmentioning
confidence: 90%
See 3 more Smart Citations
“…Likewise, offices and homes had comparably low ∑SCCP concentrations ranging 5-31 and 11-14 µg/g in a limited number of Taiwanese dust samples (n=4) [16]. On the other hand, reported offices to be the least contaminated indoor environments amongst Chinese indoor microenvironments assessed with respect to both SCCP and MCCP homologues [29]. CP levels measured in a limited number of office samples from outside China have usually exceeded levels seen in homes.…”
Section: Chlorinated Paraffinsmentioning
confidence: 90%
“…Levels in the dust of Chinese homes have typically exceeded those of samples from North America or Europe, perhaps due to China's role as the world largest CP manufacturer. [29] reported similarly elevated mean ∑SCCP and ∑MCCP levels combined from Chinese homes, workplaces and dormitories of 148 and 139 µg/g, while ∑SCCPs averaged 49 µg/g in dust from Chinese apartments (medians n.a.) [55].…”
Section: Chlorinated Paraffinsmentioning
confidence: 95%
See 2 more Smart Citations
“…The first manual of exposure parameters was published in the United States as early as 1989 [34], while China did not publish the first edition until 2013. Most of the existing studies adopted the parameters of the United States [35,36] or did not consider the modification effect of the parameters on outcomes at all [37,38] ,which may lead to unreliable conclusions. For example, Wang et al had found that if the inhalation rates of the United States were used directly in China, the error would be 2.6% to 30.9%, which would increase the uncertainty of health risk assessment results [39].…”
mentioning
confidence: 99%